AKTIVITAS IMUNOMODULATOR EKSTRAK ETANOL SPONS Callyspongia sp. TERHADAP FAGOSITOSIS MAKROFAG PADA MENCIT JANTAN BALB/C. - Muhammad Ilyas Y.; Asriullah Jabbar; Mentarri Bafadal; Muhammad Hajrul Malaka; Firdayanti Firdayanti; I. Sahidin (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2020)
Sponge Callyspongia sp. has compounds that act as immunomodulatory agents, one of which is flavonoids.Flavonoids have the potential to be immunostimulants by increasing the phagocytic activity of macrophages. This study was experimental with a post test only control group design method. This study used 24 micemalestrain Balb /c with a body weight of 20-30 grams divided into 6 groups. The first group get extracts of sponge Callyspongia sp. 100 mg/kgBW, second group get the extract of sponge Callyspongia sp. 200 mg/kgBW, third group get extracts of sponge Callyspongia sp. 300 mg/kgBW, fourth group get the extract of sponge Callyspongia sp. 400 mg/kgBW, positive control group was given Stimuno® 0,13 mg/kgBW and the negative control group get Na-CMC 0.5%. A test given in orally preparations on the first day until the seven day. On the eighth day of each of the mice are injected bacteria Staphylococcus aureus (SA) by intraperitoneal. The activity of macrophage cells from murine peritoneal fluids sweep by calculating the percentage of macrophages that does phagocytosis of 100 cells are observed. The data obtained were then analyzed by one way Anova statistics and test post hoc Tukey's. As result, the are that ethanol extracts of sponge Callyspongia sp. at doses of 300 mg/kgBW and 400 mg/kgBW have potential as immunomodulator with based on results of statistical tests post hoc Tukey (P > 0.05) showed no meaningful difference against the positive control (Stimuno ®) wich improving the activity of the cells of the macrophage phagocytosis.